A Profile of an Endosymbiont-enriched Fraction of the Coral Stylophora pistillata Reveals Proteins Relevant to Microbial-Host Interactions - Weston, Andrew J.; Dunlap, Walter C.; Shick, J. Malcolm; Klueter, Anke; Iglic, Katrina; Vukelic, Ana; Starcevic, Antonio; Ward, Malcolm; Wells, Mark L.; Trick, Charles G.; Long, Paul F. (Molecular & cellular proteomics, 2012)
This study examines the response of Symbiodinium sp. endosymbionts from the coral Stylophora pistillata to moderate levels of thermal “bleaching” stress, with and without trace metal limitation. Using quantitative high throughput proteomics, we identified 8098 MS/MS events relating to individual peptides from the endosymbiont-enriched fraction, including 109 peptides meeting stringent criteria for quantification, of which only 26 showed significant change in our experimental treatments; 12 of 26 increased expression in response to thermal stress with little difference affected by iron limitation. Surprisingly, there were no significant increases in antioxidant or heat stress proteins; those induced to higher expression were generally involved in protein biosynthesis. An outstanding exception was a massive 114-fold increase of a viral replication protein indicating that thermal stress may substantially increase viral load and thereby contribute to the etiology of coral bleaching and disease. In the absence of a sequenced genome for Symbiodinium or other photosymbiotic dinoflagellate, this proteome reveals a plethora of proteins potentially involved in microbial-host interactions. This includes photosystem proteins, DNA repair enzymes, antioxidant enzymes, metabolic redox enzymes, heat shock proteins, globin hemoproteins, proteins of nitrogen metabolism, and a wide range of viral proteins associated with these endosymbiont-enriched samples. Also present were 21 unusual peptide/protein toxins thought to originate from either microbial consorts or from contamination by coral nematocysts. Of particular interest are the proteins of apoptosis, vesicular transport, and endo/exocytosis, which are discussed in context of the cellular processes of coral bleaching. Notably, the protein complement provides evidence that, rather than being expelled by the host, stressed endosymbionts may mediate their own departure.